Developing intercultural competence through English focus on Ukrainian and Polish cultures - Niżegorodcew, Anna; Bystrov, I͡A. V.; Kleban, Marcin (Jagiellonian University Press, 2011)
The volume Developing Intercultural Competence through English: Focus on Ukrainian and Polish Cultures edited by Anna Niżegorodcew, Yakiv Bystrov and Marcin Kleban offers a valuable result of a joint intercultural project between two universities from the neighbouring countries of Poland and Ukraine. Among the mass of books on intercultural communication the proposed volume distinguishes itself by three features: unusual format combining the work of both scholars and students, the focus on the intracultural approach, and practical designation. It also stresses the increasing awareness in the modern world that teaching/learning English serves the purpose of developing general intercultural competence and not building the knowledge about the English speaking world. [...] The choice of topics [...] indicates an interesting cultural difference - Ukrainiar inclination to focus on the characteristic and attractive aspects of their own culture and Polish on the problematic and the difficult